Applying online parental guided self-help family-based treatment for adolescent anorexia nervosa: A comparison to family-based treatment delivered by videoconferencing. (July 2022) - Couturier, Jennifer; Webb, Cheryl; Carson, Natalie; Doxtdator, Kyrsten; Matheson, Brittany; Datta, Nandani; Sami, Sadaf; Citron, Kyra; Lock, James
Guided self-help has become an important treatment option in the field of eating disorders as access to in person evidence-based treatments is limited. Given the scant amount of literature published on guided self-help for the treatment of eating disorders in the child and adolescent population, our aim was to describe online GSH-FBT sessions in detail as conducted as part of a larger feasibility study, examining quotations from therapists that illustrate the GSH-FBT stance and also describing how online GSH-FBT differs from FBT delivered by videoconferencing within a descriptive case report.